Mass outflow of the X-ray emission line gas in NGC 4151. Issue Volume 15:Issue S359(2020) (March 2019) - Kraemer, S. B.; Turner, T. J.; Crenshaw, D. M.; Schmitt, H. R.; Revalski, M.; Fischer, T. C.
Abstract: We have analyzed Chandra /High Energy Transmission Grating spectra of the X-ray emission line gas in the Seyfert galaxy NGC 4151. The zeroth-order spectral images show extended H- and He-like O and Ne, up to a distance r ˜ 200 pc from the nucleus. Using the 1st-order spectra, we measure an average line velocity ˜230 km s –1, suggesting significant outflow of X-ray gas. We generated Cloudy photoionization models to fit the 1st-order spectra; the fit required three distinct emission-line components. To estimate the total mass of ionized gas ( M ) and the mass outflow rates, we applied the model parameters to fit the zeroth-order emission-line profiles of Ne IX and Ne X. We determined an M ≍ 5.4 × 10 5 M ʘ . Assuming the same kinematic profile as that for the [O III] gas, derived from our analysis of Hubble Space Telescope /Space Telescope Imaging Spectrograph spectra, the peak X-ray mass outflow rate is approximately 1.8 Mʘ yr –1, at r ˜ 150 pc. The total mass and mass outflow rates are similar to those determined using [O III], implying that the X-ray gas is a major outflow component. However, unlike the optical outflows, the X-ray emitting mass outflow rate does not drop off at r > 100pc, which suggests that it may have a greater impact on the host galaxy.